2017
DOI: 10.21769/bioprotoc.2571
|View full text |Cite
|
Sign up to set email alerts
|

DQ-Red BSA Trafficking Assay in Cultured Cells to Assess Cargo Delivery to Lysosomes

Abstract: Lysosomes are the terminal end of the endocytic pathway having acidic environment required for active hydrolases that degrade the cargo delivered to these compartments. This process of cargo delivery and degradation by endo-lysosomes is a tightly regulated process and important for maintaining cellular homeostasis. Cargos like EGF (Epidermal Growth Factor), Dil-LDL (3,3'-Dioctadecylindocarbocyanine-Low Density Lipoprotein), Dextran, DQ-BSA (Dye Quenched-Bovine Serum Albumin) are routinely used by researchers t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
118
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(122 citation statements)
references
References 7 publications
4
118
0
Order By: Relevance
“…We confirmed that the inhibitor treatment did block lysosomal degradation by incubating cells with dye-quenched bovine serum albumin (DQ BSA) in addition to the lysosomal inhibitors. DQ BSA is self-quenched until it is digested in the lysosome (59, 60), and imaging confirmed that cells treated with lysosome inhibitors did not fluoresce, but cells treated with the vehicle control (H 2 O) did, as expected (Fig. 5B).…”
Section: Resultssupporting
confidence: 70%
“…We confirmed that the inhibitor treatment did block lysosomal degradation by incubating cells with dye-quenched bovine serum albumin (DQ BSA) in addition to the lysosomal inhibitors. DQ BSA is self-quenched until it is digested in the lysosome (59, 60), and imaging confirmed that cells treated with lysosome inhibitors did not fluoresce, but cells treated with the vehicle control (H 2 O) did, as expected (Fig. 5B).…”
Section: Resultssupporting
confidence: 70%
“…To assess if the increased pH had an impact in lysosomal proteolytic activity, we loaded the control and both RC-kd cell lines (to verify whether both RC-kd lines behave comparably also in key functional assays) with polymeric bovine serum albumin labelled with a green BODIPY dye (DQ Green BSA green; the assay is based on the fact that the high amount of fluorophore in polymeric DQ Green BSA has a quenching effect). Cells take up DQ Green BSA by endocytosis and it accumulates in the lysosomes [27]. As the lysosomal proteases hydrolyze DQ Green BSA into small peptides, in which the fluorescence is no longer quenched, the fluorescent monomers accumulate and an increase in fluorescence is observed (Figure 2(b)).…”
Section: Mitochondrial Respiratory Chain Malfunction Impairs Lysosomamentioning
confidence: 99%
“…The mCherry-AHA1 and GFP-SYP132 protein distribution at the cell periphery relative to the cell interior was determined by tracing around retracted cell periphery, region of interest (ROI) width ;1.5 mm, and the interior of each cell using the bright-field overlay for reference. Integrated fluorescence density within the ROIs marking the periphery and interior of each cell was measured, and corrected total fluorescence for each ROI was calculated following background subtraction (Marwaha and Sharma, 2017). When coexpressed with GFP-SYP132, the periphery-internal corrected total fluorescence ratio for mCherry-AHA1 was lower compared with when mCherry-AHA1 was expressed on its own or with GFP-SYP121 ( Fig.…”
Section: Syp132 Modulates Aha1 Localization At the Plasma Membranementioning
confidence: 99%
“…For each cell, ROIs demarcating cell periphery (width of ;1.5 mm) and cell interior were traced using the bright-field image overlay as reference. Integrated fluorescence density was measured using Fiji (National Institutes of Health) software for each ROI and corrected for background fluorescence using the equation [corrected total fluorescence = integrated density -(area of selected ROI 3 mean fluorescence of background)], as described (Marwaha and Sharma, 2017). The proportion of fluorophore distribution at the cell periphery and interior was represented as bar graphs of mean peripheral-internal fluorescence ratios.…”
Section: Cell Peripheral-internal Fluorescence Distributionmentioning
confidence: 99%